Structural response monitoring of concrete beam under flexural loading using smart carbon black/cement-based sensors - Dong, Wenkui; Li, Wengui; Luo, Zhiyu; Long, Guodong; Vessalas, Kirk; Sheng, Daichao (Smart materials and structures, 2020)
The fractional changes of resistivity (FCR) of cement-based sensors with various carbon black (CB) contents were firstly investigated under uniaxial compression in this study. Then the piezoresistive behaviours of embedded cement-based sensors in unreinforced small-scale concrete beams were investigated under flexural bending load. As for the embedded cement-based sensors in the compression zones of the beam, the stress magnitude and crack failure initiation of the beams can be detected and monitored by a gradual decrease and then a sharp increase in the FRC. On the other hand, as for the counterpart sensors in the tension zones of the beam, the stress magnitude and crack failure initiation can be recognized by the gradual increase in resistivity and then a rapid jump in the FRC. During the stress monitoring of the concrete beam, the FCR values of cement-based sensors in both the compression and tension zones were consistent with the flexural stress changes, which exhibit acceptable sensitivity and reversibility. Moreover, very firm and dense interfaces in the boundaries indicate the excellent cohesion between embedded CB/cement-based sensors and beams. The related results demonstrate that the CB/cement-based sensors embedded in concrete exhibit excellent piezoresistive behaviours to potentially monitor the stress magnitude and failure process of concrete structures and pavements.